2012
DOI: 10.17221/5568-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocin-producing lactic acid bacteria as a probiotic potential from Thai indigenous chickens

Abstract: Bacteriocin-producing lactic acid bacteria (LAB) were isolated and screened from the gastrointestinal tract (GIT) of Thai indigenous chickens. The bacteriocinogenic activities and the primary probiotic properties were determined. The bacteriocins produced by 14 strains of selected LAB displayed inhibitory activity against indicator strains after the supernatants were neutralized with NaOH in the following species: Lactobacillus sakei subsp. sakei JCM1157, Enterococcus faecalis VanB, Bacillus sp., and Listeria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
(42 reference statements)
2
9
0
Order By: Relevance
“…It is well known that resistance of the indigenous laying or meat chickens (especially those produced in village societies) to different biotic and abiotic stresses, is related to presence of LAB strains with high probiotic potentials in the digestive systems of such chickens (Damayanti et al, 2012;Musikasang et al, 2012;Yamazakia et al, 2012). The presence of some lactobacilli bacteria in the chicken GIT has been described to be of great importance for regulating the composition of the intestinal microflora, developing immunity of the intestine, and promoting the health of chickens (Yamazakia et al, 2012 ;Muir et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that resistance of the indigenous laying or meat chickens (especially those produced in village societies) to different biotic and abiotic stresses, is related to presence of LAB strains with high probiotic potentials in the digestive systems of such chickens (Damayanti et al, 2012;Musikasang et al, 2012;Yamazakia et al, 2012). The presence of some lactobacilli bacteria in the chicken GIT has been described to be of great importance for regulating the composition of the intestinal microflora, developing immunity of the intestine, and promoting the health of chickens (Yamazakia et al, 2012 ;Muir et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Lactic acid bacteria (LAB), as common microorganisms in foods and the intestine of humans and most animals, are widely used as probiotics in humans and animals to restore the ecological balance of different mucosa (Chen et al, 2012;Musikasang et al, 2012). Some studies showed high effect of LAB on the economic yield properties (lay intensi-…”
Section: Introductionmentioning
confidence: 99%
“…However, the isolates could produce protease and phytase (Table 6). Musikasang et al (2012) found that LAB isolates showed the proteinase activity, but neither starch nor lipid digestions were detected. Selected LAB isolates can produce phytase that hydrolyzes phytic acid to myo-inositol and phosphoric acid.…”
Section: Assessment Of Probiotic Characteristicsmentioning
confidence: 90%
“…Musikasang et al [23] checked antibiotic sensitivity of their isolated LABs against various antibiotics. To penicillin G, all LAB strains showed high susceptibility to erythromycin (MIC < 0.25 μg/ml) and tetracycline.…”
Section: Discussionmentioning
confidence: 99%